Net present value and payback period for building integrated photovoltaic projects in Malaysia - Ong, Tze San; Chun, Hau Thum (Human Resource Management Academic Research Society, 2013)
Photovoltaic systems (PV) offer a clean, alternative energy source that is very suitable in the Malaysian climate, and consistent with the peak production and high demand in power in Malaysia. However, the application of PV systems in Malaysia is still low. The objective of this research is to determine the total cost, price/kWp system, net present value (NPV), and payback period for PV project in Malaysia. All seven projects were selected and used for the analysis and named as Project 1 to 7. The findings from this research indicate that all seven projects show a negative NPV value and payback period is more than thirty eight years. Four projects even get payback period of more than fifty years. However, an interesting projection on the price reduction shows that a positive NPV is achievable if the price/kWp system reduced to RM11,000 and RM4,000 for government subsidized and non- subsidized projects respectively. The estimation on payback period is between four to eight years with the price reduction of 85% to 50% respectively from the current market price. Global warming, climate change, environment pollution and demand for energy represent critically issues with a wide array of potential environmental disasters affecting people health and safety. These issues are opening up new opportunities for utilization of renewable energy resources like solar photovoltaic system (PV). PV system has been widely applied in many countries such as German, Spain, Japan, US, UK and Australia but interestingly the application is rather low in Malaysia. Al though Malaysia is a tropical country and located in the equator with sunlight all year round, the development of PV is still in small scale and at the beginning stage. This study is designed to find out the capital costs needed to install a PV system in Malaysia, and serve as a guideline for public when considering a PV system.